ANALISIS PENERAPAN SISTEM PENGENDALIAN INTERN PEMERINTAH PADA BADAN PERENCANAAN PEMBANGUNAN DAERAH KABUPATEN MUSI RAWAS UTARA - Miki Indika; Abdika Jaya; Ninik Afrianti (LPPM Universitas Bina Insan, 2020)
The aim of this study is to analyze the government’s internal control system (SPIP) at the Development Planning Agency at Sub-National Level of Musi Rawas Utara. This study is a descriptive study that used to see t the value of independent variables of the government internal control system (SPIP). Primary data and secondary data are needed as a basis for analysis, while data collection techniques are the from of observations, interviews and documents. The analytical technique used is desciptive. The results of the analysis showed that planning agency at sub – national level of Musi Rawas Utara in 2018 was in accordance with government regulation No. 60 year 2008 abaot control system internal government (SPIP).